Henry Workman Conner papers - Conner, Henry Workman, 1797-1861.
Miscellaneous letters to Conner from Armistead Burt, John Caldwell Calhourn, and Francis Wilkinson Pickens. Also letters from John C. Calhoun to F.H. Elmore and Henry Gourdin.
Photostats (negative).
Banker and businessman.
Collection material in English.
Keywords: Burt, A. -- 1802-1883 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Elmore, F. H. -- 1799-1850 -- Correspondence; Gourdin, Henry, -- 1804-1879 -- Correspondence; Pickens, F. W. -- 1805-1869 -- Correspondence